High-rate deformation and spall fracture of hadfield steel under action of high-current nanosecond relativistic electron beam; Technical Physics Letters; Vol. 36, iss. 9 - Gnyusov S. F. Sergey Fedorovich; Rotshtein V. P.; Polevin S. D.; Kitsanov S. A. (2010, 2010)
Title screen